Wave Interaction with an Emerged Porous Media (Advances in Applied Mathematics and Mechanics, 2014)
In this paper, we study wave interaction with an emerged porous media.The governing equation is shallow water equations with a frictionterm of the linearized Dupuit-Forcheimer's formula. From the continuity of surface andhorizontal flux, we derived the wave reflection and transmission coefficient formulas.They are similar to the corresponding formulas of the submerged solid barbreakwater. We solve the equations numerically using finite volume method ona staggered grid. The numerical wave reduction in the porous media confirms theanalytical wave transmission curve.